The Role Of Helmet Use On Severity Of Maxillofacial Injuries Among Electric-Powered Bikes, Scooters And Motorcycle Accidents Attending Hafr Central Hospital (Journal of Namibian Studies : History Politics Culture, 2023)
Background: Maxillofacial injuries are among the most typical forms of body injuries. Facial bone fractures, dentoalveolar injuries and soft tissue injuries are the three categories of maxillofacial injuries. Automobile accidents, attacks, falls, and athletic injuries are all possible causes. This study aimed to determine the role of helmet use on the severity of oral maxillofacial injuries among electric bike and motorcycle accidents attending Hafr Central Hospital, Saudi Arabia.Materials and methods: This study was a descriptive study of the injured motorcyclist, electric power bikes, and scoters seen with maxillofacial injuries between January 2021 and January 2023 at Emergency Hafr central hospital in Hafr albaten city. The study was a cross-sectional study that included patients reported within the previous three years. The source population consisted of maxillofacial injury patients who presented to the accident department after being involved in an electric-powered bike, scooter, or motorbike accident, as well as the oral and maxillofacial surgery department at Hafr Cental hospital in Eastern Provence. Data were entered into Microsoft Excel soft Simple descriptive statistical, chi-square test, and Kruskal-Wallis test was applied as appropriate. Statistical significance was inferred at p